THE EFFECT OF THE EXISTENCE OF 35 CONVENIENCE STORES ON CHANGES IN CONSUMER INTERESTS IN SEKADAU DISTRICT - Fitria Elvi; Florentina Neneng Sabela; Jonathan Giovanni (SEAN Institute, 2023)
The existence of a new store is a competitor to other stores, the existence of several 35 department stores in Sekadau district can change consumer tastes or consumer interest in shopping. qualitative research method, which is carried out by taking samples from several consumers and employees of department stores 35 by way of observation and interviews. So the results of this study were that the existence of several 35 department stores in Sekadau district was able to change consumer interest in shopping from traditional markets to 35 department stores